2006
DOI: 10.1007/s00213-006-0446-8
|View full text |Cite
|
Sign up to set email alerts
|

Dose effects of triazolam on brain activity during episodic memory encoding: a PET study

Abstract: Results are consistent with behavioral evidence that benzodiazepines impair prefrontal control processes as well as contextual memory and episodic binding processes thought to be controlled by the medial temporal lobe. In addition to elucidating the brain mechanisms underlying these benzodiazepine-induced behavioral deficits, results of this study also help validate hypotheses generated in nonpharmacological neuroimaging studies regarding the processes controlled by these brain regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 76 publications
(92 reference statements)
1
11
0
Order By: Relevance
“…This would fit neatly with the pattern of effects observed here, that is, lack of drug effects in the validation phase of maintenance and reasoning problems with visuospatial relations, a smaller effect in dealing with visual stimuli, that was equivalent in the validation phase of both reasoning and maintenance tasks, culminating in a larger effect when the manipulation of subiconic relations was required. This would also be in line with findings of central executive/prefrontal impairment in other BZ studies using different test measures (Rusted et al 1991;Coull et al 1995Coull et al , 1999Mintzer and Griffiths 2003;Mintzer et al 2006). This hypothesis is easily supported for the difference between the visuospatial and subiconic relations.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This would fit neatly with the pattern of effects observed here, that is, lack of drug effects in the validation phase of maintenance and reasoning problems with visuospatial relations, a smaller effect in dealing with visual stimuli, that was equivalent in the validation phase of both reasoning and maintenance tasks, culminating in a larger effect when the manipulation of subiconic relations was required. This would also be in line with findings of central executive/prefrontal impairment in other BZ studies using different test measures (Rusted et al 1991;Coull et al 1995Coull et al , 1999Mintzer and Griffiths 2003;Mintzer et al 2006). This hypothesis is easily supported for the difference between the visuospatial and subiconic relations.…”
Section: Discussionsupporting
confidence: 81%
“…What most of these studies do show is that BZs reduce the speed at which information is generally processed in WM (Curran 2000;Reder et al 2006). In some cases, the central executive is cited as being the affected subsystem (Rusted et al 1991;Coull et al 1995Coull et al , 1999Mintzer and Griffiths 2003;Mintzer et al 2006). It is therefore difficult to determine if the BZ-induced slowing of reasoning is due to alterations of central executive functioning or to specific slowing of visuospatial or phonological/verbal processing, which have not been adequately investigated in the BZ literature.…”
Section: Introductionmentioning
confidence: 93%
“…38 These results were later replicated in a similar study which found that triazolam produced dose-related impairment in memory performance and dose-related deactivation in brain regions previously shown to be associated with memory encoding and known to show differential activity or connectivity in PTSD, such as the anterior cingulate cortex, prefrontal cortex and parahippocampal gyrus. 39 Dosedependent decreases in brain activation in the bilateral amygdala and insula have also been reported in response to lorazepam (1-time dosing) as compared with placebo during an emotion face assessment task in healthy volunteers, 40 rendering these studies equally relevant for PTSD research. The effects of methamphetamine on cerebral activity have been examined using dynamic gradient-echo imaging before, during and after intravenous administration in healthy controls.…”
Section: Direct Effects Of Psychotropic Medications On Cbf In Healthymentioning
confidence: 99%
“…37 The effects of benzodiazepines on brain activation during memory encoding tasks have been investigated. 38,39 Studies using PET revealed that triazolam significantly impaired memory performance and led to deactivation in brain areas previously shown to be associated with memory encoding, including the anterior cingulate cortex, precuneus and cerebellum. 38 These results were later replicated in a similar study which found that triazolam produced dose-related impairment in memory performance and dose-related deactivation in brain regions previously shown to be associated with memory encoding and known to show differential activity or connectivity in PTSD, such as the anterior cingulate cortex, prefrontal cortex and parahippocampal gyrus.…”
Section: Direct Effects Of Psychotropic Medications On Cbf In Healthymentioning
confidence: 99%
“…Apart from anti-depressant agents, a non-negligible number of patients (n = 17) received benzodiazepine (loracepam) medication on demand. This is particularly critical as benzodiazepines have been shown to influence cognition on the behavioural and neurofunctional (ACC) level (Mintzer et al, 2006;Munoz-Torres et al, 2011). Among other cognitive domains, error monitoring processes have been shown to be affected (Bruijn et al, 2004).…”
Section: Limitationsmentioning
confidence: 99%